2021
DOI: 10.3389/fphys.2021.629532
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Ceramidase Is Required for the Reproduction of Brown Planthopper, Nilaparvata lugens (Stål)

Abstract: Ceramides are bioactive sphingolipids that have been implicated in insect development; however, their role in insect reproduction remains poorly understood. Here, we report the pivotal role of neutral ceramidase (NCER) in the female reproduction of the brown planthopper (BPH), Nilaparvata lugens (Stål), a significant pest in rice cultivation in Asia. LC-MS/MS demonstrated that, among different developmental stages of BPH, the levels of ceramides were highest in 1st instar nymphs and lowest in adults. The trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Ceramide is located at the center of sphingolipid metabolism [ 58 ]; studies have shown that abnormal accumulation of ceramide can negatively impact insect reproduction, particularly affecting female adults of N. lugens . This abnormal accumulation results in delayed maturation of oocytes, decreased oviposition, and diminished offspring survival rate [ 59 ]. Insects exhibit characteristics of being small, fast-growing, and short-lived, leading them to adopt the “r-selection” reproductive strategy emphasizing high fecundity to ensure population continuation and success through quantity rather than quality.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide is located at the center of sphingolipid metabolism [ 58 ]; studies have shown that abnormal accumulation of ceramide can negatively impact insect reproduction, particularly affecting female adults of N. lugens . This abnormal accumulation results in delayed maturation of oocytes, decreased oviposition, and diminished offspring survival rate [ 59 ]. Insects exhibit characteristics of being small, fast-growing, and short-lived, leading them to adopt the “r-selection” reproductive strategy emphasizing high fecundity to ensure population continuation and success through quantity rather than quality.…”
Section: Discussionmentioning
confidence: 99%
“…The alCDase of Drosophila ( Dacer ) was highly expressed in the pupal stage and significantly affected the longevity of Drosophila ( Yang et al, 2010 ; Zhang et al, 2019 ). The nCDase of Tribolium castaneum showed high expression in adults, but its biological functions had not been demonstrated ( Zhou et al, 2011 ).The nCDase of BPH was highly expressed in female adults and played essential roles in the reproduction of the insect ( Shi et al, 2018 ; Shi et al, 2021 ). Different from BPH or Tribolium castaneum , both ClNC and ClAC had high expression in the early nymph stages.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the lipid biosynthetic process, sphingolipids are an important class of lipids that participate in crucial events of cell proliferation, differentiation, and apoptosis in various species [ 46 ]. Recently, evidence has accumulated to show that sphingolipids have roles in the signaling pathways involved in reproduction and oocyte development of N. lugens [ 47 , 48 , 49 ]. Cyclin-dependent kinase (CDK) is a serine/threonine protein kinase family that cooperates with cyclin and is required for embryo development and cell cycle progression [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BPHs were reared on susceptible rice seedlings cv. Taichung Native 1 (TN1) at 27 ± 1 • C, 70% relative humidity, and a 16:8 h light: dark photoperiod as described in a previous study [47]. All samples were frozen in liquid nitrogen immediately and stored at −80 • C. Total RNA was extracted using TRIzol Reagent (Invitrogen, Carlsbad, CA, USA) according to the manufacturer's protocol.…”
Section: Sample Collection and Total Rna Extractionmentioning
confidence: 99%